Alkali-activated concrete: Engineering properties and stress–strain behavior. (15th September 2015) - Thomas, Robert J.; Peethamparan, Sulapha
Highlights: The engineering properties of alkali-activated concretes (AAC) are determined. Results are compared to existing models for portland cement concrete (PCC). Models are proposed to predict tensile strength and modulus of AAC. AAC exhibits higher tensile strength and lower Poisson's ratio than PCC. Alkali-activated slag concrete is much more brittle than PCC. Abstract: This paper presents an investigation into the tensile strength, modulus of elasticity, Poisson's ratio, and stress–strain relationships of alkali-activated portland-cement-free concrete made with fly ash or ground granulated blast furnace slag (GGBFS) as the sole binder. Alkali-activated concrete is shown to be stronger in tension and have lower Poisson's ratio than portland cement concrete. Relationships are proposed to estimate the tensile strength and modulus of elasticity based on the compressive strength of alkali-activated concrete, which are of the same form as those currently employed for portland cement concrete.